2014
DOI: 10.1080/0158037x.2014.967346
|View full text |Cite
|
Sign up to set email alerts
|

Differential outcomes of adult education on adult learners' increase in social inclusion

Abstract: To date a significant share of the European population can be considered at risk of social exclusion. It has been argued that adult education programmes are a powerful tool to support vulnerable adults increasing their social inclusion. This study aims to answer the question if and which subgroups of vulnerable adults experience an increase in social inclusion after joining adult education programmes. The results of our study show that 46.3% of the participants experience an increase of social inclusion in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…De Greef et al (2014) found that groups with different ethnic backgrounds perceive differences in the rate of increase in social inclusion: non-natives report higher increases with respect to going out and meeting people. People who are living together and low-educated adults also report more positive changes in their social inclusion (De Greef et al, 2014). Furthermore, the Benefits of Lifelong Learning-project (BeLL) (Manninen et al, 2014) reports that adults with lower educational background, females and older adults experience more positive changes to social engagement.…”
Section: Indicated Thatmentioning
confidence: 99%
See 3 more Smart Citations
“…De Greef et al (2014) found that groups with different ethnic backgrounds perceive differences in the rate of increase in social inclusion: non-natives report higher increases with respect to going out and meeting people. People who are living together and low-educated adults also report more positive changes in their social inclusion (De Greef et al, 2014). Furthermore, the Benefits of Lifelong Learning-project (BeLL) (Manninen et al, 2014) reports that adults with lower educational background, females and older adults experience more positive changes to social engagement.…”
Section: Indicated Thatmentioning
confidence: 99%
“…The relationship between adult education and social inclusion According to De Greef et al (2014) adult learners experience an increase on social inclusion after participation in adult education courses: 41% of the participants perceived an increase in participation and connection. Field (2012) reported that social and civic engagement is closely associated with participation in adult learning.…”
Section: Indicated Thatmentioning
confidence: 99%
See 2 more Smart Citations
“…The World Bank (2007) for instance defines social inclusion in terms of financial, physical, human and social capital and emotional and functional satisfaction. Other studies define social inclusion in terms of material resources, social relations, civic activities, basic services, neighbourhood inclusion, achievement, participation and social connection (Greef, Verté, & Segers, 2015;Ogg, 2005). Migrants and ethnic minorities can be denied social inclusion due to their cultural background, linguistic differences, political or religious background or the distance between their country of origin and host country (see Dahlstedt & Bevelander, 2010).…”
Section: Theoretical Backgroundmentioning
confidence: 99%